Mechanism and control of strong rock pressure in the gully area under compound key strata - Xingping Lai; Haoyu Zhu; Pengfei Shan; Yun Zhang; Longquan Wu; Hao Qiao; Haozhou Zhao; Ziqiang Dai (Energy Science & Engineering, 2024)
Abstract In view of the problem strong rock pressure is easy to occur in coal seam mining in western gully terrain. Based on the coal seam mining conditions in the gully area under the compound key strata of Zhujiamao Coal Mine, the methods of similar simulation, theoretical calculation and analysis, numerical simulation and field measurement are adopted. The dynamic structure model of the key strata of the gully is constructed, and the mechanism and prevention and control measures of the strong rock pressure in the gully area of the working face under the compound key strata are analyzed. The research shows that the upper slope section of the gully area first undergoes rotary deformation, and then the chain structure formed by the broken block occurs sliding instability and impacts inferior key strata, resulting in strong rock pressure behavior in the working face. The calculation formula of the first breaking step distance of the main key strata rotation deformation and sliding instability during the movement of the overlying strata is derived. The calculation results show that the initial rotation deformation and sliding instability breaking step distances are 27 and 142 m, respectively, which are in good agreement with the support crushing at 145 m of the first gully. Using 3DEC numerical simulation, the stress of the second gully is reduced by 3.8 MPa after pressure relief, which verifies the position of strong rock pressure calculated by the formula and provides a theoretical basis for subsequent hydraulic fracturing. According to the mechanism, the comprehensive prevention and control measures of strong rock pressure in gully terrain are put forward. The support resistance of the working face is calculated to be 10,011 kN by the support resistance formula, and the ZY11000/14/34D hydraulic support is used. The working resistance of the calculated dangerous area after hydraulic fracturing is basically lower than 30 MPa, and the control effect is good. It has reference significance for coal seam mining through gully terrain.